The UniSpacer: correcting varus malalignment in medial gonarthrosis - Clarius, Michael; Becker, Justus Felix; Schmitt, Holger; Seeger, Jörn Bengt (International orthopaedics, 2010)
While options for operative treatment of leg axis varus malalignment in patients with medial gonarthrosis include several established procedures, such as unicompartmental knee arthroplasty (UKA), total knee arthroplasty (TKA) or high tibial osteotomy (HTO), there has been little focus on a less invasive option introduced more recently: the UniSpacer™ implant, a self-centering, metallic interpositional device for the knee. This study evaluates clinical and radiological results of the UniSpacer™, whether alignment correction can be achieved by UniSpacer™ arthroplasty and alignment change in the first five postoperative years. Anteroposterior long leg stance radiographs of 20 legs were digitally analysed to assess alignment change: two relevant angles and the deviation of the mechanical axis of the leg were analysed before and after surgery. Additionally, the change of the postoperative alignment was determined one and five years postoperatively. Analysing the mechanical tibiofemoral angle, a significant leg axis correction was achieved, with a mean valgus change of 4.7 ± 1.9°; a varus change occurred in the first postoperative year, while there was no significant further change of alignment seen five years after surgery. The UniSpacer™ corrects malalignment in patients with medial gonarthrosis; however, a likely postoperative change in alignment due to implant adaptation to the joint must be considered before implantation. Our results show that good clinical and functional results can be achieved after UniSpacer™ arthroplasty. However, four of 19 knees had to be revised to a TKA or UKA due to persistent pain, which is an unacceptably high revision rate when looking at the alternative treatment options of medial osteoarthritis of the knee.